Global Transcriptomic Analysis and Function Identification of Malolactic Enzyme Pathway of Lactobacillus paracasei L9 in Response to Bile Stress - Ma, Xiayin; Wang, Guohong; Zhai, Zhengyuan; Zhou, Pengyu; Hao, Yanling (Frontiers in Microbiology, 2018)
Tolerance to bile stress is crucial for Lactobacillus paracasei to survive in the intestinal tract and exert beneficial actions. In this work, RNA-Seq transcriptomic analysis revealed that 104 genes were significantly changed (log2FoldChange > 1.5, p <0.05) in detected transcripts of L. paracasei L9 cultured under bile stress conditions of 0.13 % Ox-bile. Bile stress can be a signal for gut entry, which could result in expansion of carbon-source utilization profiles to better adapt to the intestinal environment. Meanwhile, L9 shifted its carbohydrate metabolism flow to mixed-acid fermentation, producing more energy to enhance bile resistance. The opp operon was significantly increased at transcriptional level to increase the uptake of oligopeptides under bile stress. In addition, the cell wall was modified by the lysinylation to repulse cationic bile compounds. Furthermore, gene mleS encoding malolactic enzyme was 2.60-fold up-regulated. Meanwhile, L-malic acid was proved to enhance bile tolerance, which could be attributed to the intracellular alkalinization caused by malolactic enzyme pathway. In addition, membrane vesicles were observed under bile stress, suggesting a disturbance in membrane charge without L-malic acid. Then, genetic and physiological experiments revealed that malolactic enzyme pathway enhanced the bile tolerance by maintaining a membrane balance in L. paracasei L9.